Exercise and/or Cold Exposure Alters the Gene Expression Profile in the Fat Body and Changes the Heart Function in Drosophila - Huang, Ting; Jian, Xiaoyi; Liu, Jinglin; Zheng, Lan; Li, Fang Qiu; Meng, Ding; Wang, Tongquan; Zhang, Shihu; Liu, Yi; Guan, Zhilong; Feng, Jiadong (Frontiers in Endocrinology, 2022)
Abstract: The major reason of human morbidity and mortality is obesity and related diseases. Brown adipose tissue (BAT) is associated with low total adipose tissue content and a lower risk of type 2 diabetes mellitus. Studies have shown that exercise and cold expose may induce browning. In this study, we verified (1) whether exercise and/or cold exposure can improve the expression level of ucp4c, serca, ampkα, camkⅡ, sirt1, octβ3r, and hamlet; (2) if these interventions can save cardiac dysfunction induced by a high-fat diet (HFD) in Drosophila. w1118 (wild-type) virgin female flies collected within 8 h after eclosion were divided into eight groups: the normal feed control group (NFD-C), the normal feed exercise group (NFD-E), the normal feed cold exposure group (NFD-CA), the normal feed exercise/cold exposure group (NFD-EC), the HFD control group (HFD-C), the HFD exercise group (HFD-E), the HFD cold exposure group (HFD-CA), and the HFD exercise/cold exposure group (HFD-EC). After exercise and/or cold exposure for 7 days, the mRNA expression levels of ucp4c, serca, ampkα, camk II, sirt1, octβ3r, and hamlet were tested by qRT-PCR, and m-mode was used to assess cardiac function. In addition, we assessed the triacylglycerol (TAG) levels, motor ability, fat mass (by Oil Red O [ORO] staining), and morphological features. The results of TAG, ORO staining, and morphological features all indicate that after interventions, body size of Drosophila was smaller compared with the control group, irrespective of the feeding patterns. The mRNA expression levels of ucp4c, serca, octβ3r, hamlet, ampkα, camk II, and sirt1 were changed to varying degrees under different intervention states (exercise and/or cold exposure). Cold exposure and exercise/cold exposure partly improved cardiac function and the normal fruit flies’ cardiac function and exercise ability. However, after exercise intervention, exercise ability and heart function were improved in both HFD and normal-fat diet (NFD) fruit flies. In conclusion, different intervention states (exercise and/or cold exposure) can change the mRNA expression levels of ucp4c, serca, octβ3r, hamlet, ampkα, camk II, and sirt1. Exercise is the most effective way to restore HFD-induced cardiac dysfunction.